2022
DOI: 10.1097/hco.0000000000000981
|View full text |Cite
|
Sign up to set email alerts
|

New concepts in heart failure with preserved ejection fraction and hypertension

Abstract: Purpose of reviewHypertension (HTN) remains the most common and strongest contributing factor to the development of heart failure with preserved ejection fraction (HFpEF). In this review, we aim to summarize the pathophysiological processes linking HTN to HFpEF and highlight novel concepts in medical and device-based management of HFpEF and HTN.Recent findingsDespite the global increase in the prevalence of HFpEF, there has been limited benefit in current medication and device-based therapy for this complex sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…As an angiotensin receptor–neprilysin inhibitor, sacubitril/valsartan (sac/val) is superior to other types of antihypertensive agents because its mechanism covers both the natriuretic peptide system and RAAS, 5 showing a promising role in improving cardiovascular outcomes. 6 Sac/val has been found to be efficacious in the treatment of resistant hypertension, renal hypertension, and systolic hypertension in elderly Asian patients. 7 - 9 Additionally, a cost-utility meta-analysis based on different populations in China revealed that sac/val was cost-effective for hypertension treatment under a high willing-to-pay threshold.…”
Section: Introductionmentioning
confidence: 99%
“…As an angiotensin receptor–neprilysin inhibitor, sacubitril/valsartan (sac/val) is superior to other types of antihypertensive agents because its mechanism covers both the natriuretic peptide system and RAAS, 5 showing a promising role in improving cardiovascular outcomes. 6 Sac/val has been found to be efficacious in the treatment of resistant hypertension, renal hypertension, and systolic hypertension in elderly Asian patients. 7 - 9 Additionally, a cost-utility meta-analysis based on different populations in China revealed that sac/val was cost-effective for hypertension treatment under a high willing-to-pay threshold.…”
Section: Introductionmentioning
confidence: 99%